THE IMPACT OF NUTRITION ON HUMAN COGNITIVE FUNCTION - Lobasyuk, B.A.; Savostin, A.P.; Bodelan, M.I.; Stoyanov, O.M.; Zamkovaya, A.V.; Kalashnikov, V.I.; Zayats, L.M. (World of Medicine and Biology, 2025)
The purpose of the study was to investigate the influence of different types of populations’ nutrition on neuropsychological indexes of psychological tests. The study involved 65 healthy people aged 23 to 53 years, with an average age of 35 years. All participants were divided into 3 comparable groups. The food of participants of the first group mainly contained meat and bread. The food of the second group participants mainly contained cereals, vegetable oil, sugar and potato. Vegetables, fruits, animal products and milk were the basis of the diet of the participants in the third group. The observation period lasted for 42 days. The Benton test, adopted by B.G. Khersonsky pictogram test, the Minnesota Multifaceted Personality Inventory and the Szondi tests were used for psychological testing. Neuropsychological testing was shown to have very important diagnostic aspect, since it allows to detect the subclinical cognitive deficit presence at the early stages of this disorder. The food products consumed by a person significantly determine the humans’ individual typological characteristics and mental activity productivity. The influence of protein- and carbohydrate-containing foods on humans’ individual-typological personality traits and mental productivity was revealed. The authors conclude that nutrition improvement additionally to complex pathogenetically confirmed therapy allows to correct effectively the formed mnestic disturbances and thus contributes to cognitive reserve preservation.